Pengaruh Tambahan Penghasilan Pegawai (TPP) Terhadap Semangat Kerja Pegawai Pada Koordinator Wilayah Dinas Pendidikan Kepemudaan dan Olahraga Kecamatan Denpasar Barat Kota Denpasar - Ni Ketut Sudiarti; Ni Wayan Wahyuni (Jurnal Widya Mahavira, 2025)
This study analyzes the effect of Employee Income Supplement (TPP) on employee morale in the Regional Coordinator of the West Denpasar District Youth and Sports Office. Using the census method with 19 respondents who are the total population, this study applies a quantitative approach with data collection techniques through questionnaires and documentation. The characteristics of the respondents showed the dominance of male employees (63%), the majority were educated in S1/D4 (58%), and most were in group III (63%). The analysis of TPP variables showed good results with an average score of 51.63, where 58% of respondents gave a good rating and 42% were quite good. Based on the 15 indicators measured, the total score reached 981 with an average of 65.40. The results of the study prove that the TPP given is good and has a significant positive correlation with employee morale. The magnitude of the influence of TPP on employee morale is 19.62%, showing that financial incentives have a real contribution in increasing employee motivation and work productivity in the government environment.